2006
DOI: 10.1177/039463200601900409
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the T Cell Receptor Vβ Repertoire in a Human T Cell Resistant to Asbestos-Induced Apoptosis and Peripheral Blood T Cells from Patients with Silica and Asbestos-Related Diseases

Abstract: To explore the effects of asbestos and silica on the human immune system, an experimental model of lowdose and long-term exposure was established using a human UTLV-l-immortalized polyclonal T cell line, MT-2 (MT-20rg). MT-2 cells were continuously exposed to asbestos at a concentration (10 ug/ml) which does not induce complete cell death during short-term exposure. After acquiring resistance to CD-induced apoptosis (designated MT-2Rst), an immunological comparison was made between the MT-20rg and MT2Rst lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Parts of these findings were confirmed using clinical samples derived from patients with pleural plaque, for whom there was evidence of past asbestos exposure or malignant mesothelioma. For instance, plasma levels of IL-10 and TGF-β and gene expression of bcl-2 in peripheral CD4 + T-lymphocytes were seen to be elevated in samples from SPs compared to samples from HDs, results that were in accordance with those suggested by the results seen with the chronically-exposed MT-2 cells Nishimura et al, 2006;Maeda et al, 2008;Otsuki et al, 2009;see Figure 3). …”
Section: Disruption Of Tumor Immunity Due To Asbestos Fiberssupporting
confidence: 73%
See 1 more Smart Citation
“…Parts of these findings were confirmed using clinical samples derived from patients with pleural plaque, for whom there was evidence of past asbestos exposure or malignant mesothelioma. For instance, plasma levels of IL-10 and TGF-β and gene expression of bcl-2 in peripheral CD4 + T-lymphocytes were seen to be elevated in samples from SPs compared to samples from HDs, results that were in accordance with those suggested by the results seen with the chronically-exposed MT-2 cells Nishimura et al, 2006;Maeda et al, 2008;Otsuki et al, 2009;see Figure 3). …”
Section: Disruption Of Tumor Immunity Due To Asbestos Fiberssupporting
confidence: 73%
“…Additionally, screening for sensitivity to chrysotile asbestos revealed that the MT-2 cells and a few Epstein-Barr virus-immortalized B-lymphoblastoid cell lines were relatively more sensitive to cell death in comparison to other T-and B-lymphocyte tumor-derived lines. As it has been suggested that effects on T-lymphocytes may be more important than those on B-lymphocytes (regarding alteration of tumor immunity), this was another key reason the MT-2 cells were chosen for use in our in vitro experiments Nishimura et al, 2006;Maeda et al, 2008;Otsuki et al, 2009). …”
Section: Disruption Of Tumor Immunity Due To Asbestos Fibersmentioning
confidence: 99%
“…This overexpression was also observed when TCRVb expression in MT-2Org and MT-2Rst cell lines was compared, revealing that MT-2Rst cells overexpressed various TcRVbs. Although TcRVb-overexpressing MT-2Org cells underwent apoptosis due to their first contact with chrysotile, MT-2Rst cells showed no significant changes when they again came in contact with chrysotile [29]. These findings may be interpreted as follows: the overexpression of various TcRVbs may be the result of contact between cells and chrysotile, an asbestos fiber, during the acquisition of resistance to chrysotile-induced apoptosis caused by long-term and low-dose exposure to chrysotile [29].…”
Section: T Cell Receptor (Tcr)vb Expressionmentioning
confidence: 87%
“…ARDs showed a limited overexpression of TcRVβ without clonal expansion, whereas SILs showed a significant overexpression of TcRVβ 7.2. These experimental and clinical analyses indicate the superantigenic and dysregulation of the autoimmunity-inducing effects of asbestos and silica, respectively (71).…”
Section: Immunological Effects Of Chrysotile Asbestosmentioning
confidence: 93%